Sistem Pendeteksi Gejala Stunting pada Anak dengan Metode Certainty factor Berbasis Website - Chafidin, Afiyan Nur; Triayudi, Agung; Andrianingsih, Andrianingsih (KITA Institut, 2022)
The purpose of this study is to design and develop a stunting symptom detection system in children using the Website-based certainty factor method which aims to create a stunting symptom detection system in children from an early age and help parents in maintaining nutrition in their children, indirectly said to be computerized to detect stunting means that when applied, it makes it easier for parents to monitor nutrition quickly and precisely. This study uses a system development method where the model used is Waterfall. The results of this study are in the form of an application that provides several symptoms of stunting in children then the user can conduct consultations to determine the calculation of the results of stunting symptoms correctly. The use of this certainty factor method is implemented in an expert system that is used to look for symptoms caused by stunting and in solving the case, the certainty factor obtains an accuracy of 80%.